A Broadband Low-RCS Circularly Polarized Meta-Antenna - Zhou, Hongkun; Wang, Yuchao; Liu, Chengguo; Zhang, Cheng (Frontiers in Physics, 2022)
A low-profile circularly polarized (CP) meta-antenna with broadband low-RCS feature is proposed in this paper. Our design is the combination of a CP antenna with a chessboard polarization conversion metasurface (CPCM) for balancing the radiation property and stealth feature. To relieve the adverse effect of the CPCM on the entire radiation performance, several redundant meta-atoms with the opposite phase state are removed to enhance the realized gain during the operation bandwidth (8.0 GHz to 9.0 GHz). The proposed meta-antenna shows excellent radiation performance: −10 dB impedance relative bandwidth is 26.48% (6.78-8.85 GHz), and 3-dB axial ratio relative bandwidth is 22.03% (7.27-9.07 GHz). In addition, RCS reduction over 5 dB is achieved via our design from 8.5 GHz to 21.5 GHz (86.67%) with the help of the deliberately designed CPCM. The final measured results demonstrate great consistent with the simulated ones.